PELATIHAN LITERASI PENELITIAN PADA MAHASISWA MANAJEMEN FEB UNM - Aslam, Annisa Paramaswary; Haeruddin, M. Ikhwan Maulana; Haeruddin , Muhammad Ilham Wardhana; Hasdiansa, Ilma Wulansari; Amin, Andi Mustika (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
This activity was carried out as research literacy training for FEB UNM management students. The aim of this activity is to develop the skills and abilities of management students in compiling theses and to increase students' understanding and understanding of scientific articles. This activity took place on December 10 2022 at the BU Building of the Faculty of Economics and Business, Makassar State University (FEB UNM) which was attended by 25 participants from the FEB UNM management study program. The method for carrying out this activity is lecture and question and answer. Assessment tools in the form of tests and observations. The team conducted tests in two stages, namely pre-test and post-test which aimed to measure and accept participants for this training. The pre-test score obtained before carrying out the literacy training was 65. Meanwhile, the post-test result displayed was 80. From these results it was found that there was an increase in ability to understand and manage the material studied during the training. This is shown by the average score of participants when answering the tests given by the service team.